Fuel-rich ammonia catalytic combustion on gadolinium-doped ceria (GDC) supported copper oxide catalyst - Wang, Siqi; Ibrahim Muhammad, Haliru; Shen, Ziqi; Zhu, Mingming (Taylor & Francis, 2025)
Ammonia combustion faces challenges such as high ignition temperature, low flame speed, and potential NOx emissions. Catalytic combustion offers an alternative solution to burn ammonia with high efficiency while minimizing NOx formation. This study aims to develop a fuel-rich, catalytically stabilized ammonia combustion and study the reactivity and NOx formation of a novel gadolinium-doped ceria (GDC) supported CuO catalyst (CuO/GDC). The CuO/GDC catalyst was synthesized using the wet impregnation method and characterized using physisorption, X-ray diffraction (XRD), scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX), and Transmission Electron Microscopy (TEM). Its performance was tested in a fixed-bed reactor and compared to CuO/γ-Al2O3, with an equivalence ratio (ER) of 1.5 and temperatures ranging from 100°C to 800°C. The reaction mechanism of ammonia combustion over CuO/GDC was investigated with X-ray photoelectron spectroscopy (XPS) analysis and microkinetic modeling integrated with Density Functional Theory calculations. The CuO/GDC catalyst demonstrated a high NH3 conversion of 100% with a great N2 selectivity of over 99% at 800°C and minimal NOx formation, which was attributed to the strong adsorption of N and O species on its surface and mitigation of nitrogen oxide formation. Apart from altering the overall adsorptive properties of the catalyst, the mixed ionic-electronic conductivity of GDC also facilitates oxygen ion transport on the catalyst surface, promoting redox-driven catalytic activity. These findings highlight the potential of the use of mixed conductor as an effective catalyst support for fuel-rich ammonia catalytic combustion.
Keywords: 40 Engineering; 4017 Mechanical Engineering; 4002 Automotive Engineering; Energy; 4004 Chemical engineering; Ammonia; catalytic combustion; copper oxide catalysts; mixed conductor support